Transformasi Fragmen Tembikar dan Keramik di Situs Kota Lama, Indragiri Hulu, Riau - Stanov Purnawibowo; Baskoro Daru Tjahjono (Berkala Arkeologi Sangkhakala, 2016)
AbstractStudy on the transformation of pottery and ceramic fragments at Kota Lama Site, Indragiri Hulu, Riau is a study that scrutinizes the formation process of archaeological data. The formation process is identified through artifactual and contextual data resulted from an archaeological excavation at the site in 2016. The problem to be uncovered is the transformation process of archaeological data at Kota Lama site to reveal the formation of data and context found at the site. The research was carried out using the inductive chain of thought, which uses data classifications of fragments of pottery, ceramics, and coin-shaped terracotta objects called gacuk, as well as matrix, provenience, and association during the early phase. Analyses on artifactual data include quantitative, typological/morphological (form), spatial, and temporal ones. Contextual data were analyzed using morphological and their positions. Furthermore, those data were elaborated one with another to identify their type of context in order to understand their formation process that occurred at the site. In the last part, there are in general two contexts at the site, which are primary and secondary contexts.AbstrakKajian transformasi fragmen tembikar dan keramik di situs Kota Lama, Indragiri Hulu, Riau merupakan kajian untuk menelaah proses pembentukan data arkeologi yang diidentifikasi melalui data artefaktual dan data kontekstual yang dihasilkan dalam ekskavasi arkeologis di situs tersebut tahun 2016. Penelitian dilakukan dengan alur induktif yang menggunakan pemerian data fragmen tembikar, keramik, gacuk, matriks, provinience, dan asosiasi pada tahap awal. Analisis yang dilakukan pada data  artefak menggunakan analisis kuantitif, bentuk, keruangan, dan waktu. Adapun data konteks dianalisis mengunakan analisis morfologi dan posisinya. Selanjutnya data tersebut digabungkan satu dengan lainnya untuk mengidentifikasi jenis konteks untuk mengetahui proses pembentukan data yang terjadi di situs tersebut. Hasilnya, transformasi data arkeologi di situs Kota Lama membentuk dua buah konteks, yaitu konteks primer dan konteks sekunder